African swine fever virus rapid detection assays evaluation - Lacasta, Anna; Oba, Peter; Dione, Michel M. (ILRI, 2023)
African swine fever (ASF) is a highly fatal disease of pigs. It is a threat to the pig industry as it lowers production and significantly impacts on livelihoods of small-scale producers, while outbreaks continue to be reported in Africa, Europe, Asia, and more recently in the Caribbean. There are no globally available treatment nor commercial vaccines against ASF.